Influence of Agricultural Trade Publications on the News Agendas of National Newspapers and News Magazines - Sharienne Sweeney; C. Ann Hollifield (Journal of Applied Communications, 2000)
This study investigated whether news coverage in agricultural trade publications influenced the reporting agendas of national newspapers and national news magazines on a key agricultural industry issue. The study found more evidence that agricultural trade publications' news agendas were influenced by the reporting in national newspapers than the reverse. The findings suggest that because of major daily news organizations' greater organizational resources and readership of potential investors, they have a competitive advantage over trade publications in covering industry stories, despite the greater topical expertise that the trade publications may have.